2006
DOI: 10.1203/01.pdr.0000203180.79636.98
|View full text |Cite
|
Sign up to set email alerts
|

Novel Kinetic Insights into Treatment of Unconjugated Hyperbilirubinemia: Phototherapy and Orlistat Treatment in Gunn Rats

Abstract: ABSTRACT:Treatment with phototherapy or with the lipase inhibitor orlistat decreases plasma unconjugated bilirubin (UCB) concentrations in hyperbilirubinemic Gunn rats. We investigated the mechanism(s) underlying the effects of orlistat, phototherapy, and combined treatment, using steady-state 3 H-UCB kinetics. After three weeks of treatment with orlistat (200 mg/kg chow), phototherapy (19 W/cm 2 /nm) or combined treatment, tracer 3 H-UCB was administered IV to treated and untreated (control) Gunn rats. Plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…Previously, we showed a similar relationship between plasma UCB concentration and fecal fat excretion in Gunn rats (18). The hypobilirubinemic effect of orlistat in Gunn rats is partially due to increased metabolism of UCB to derivatives (17). Others have also shown the importance of the intestinal microflora for UCB metabolism (26).…”
Section: Discussionsupporting
confidence: 55%
“…Previously, we showed a similar relationship between plasma UCB concentration and fecal fat excretion in Gunn rats (18). The hypobilirubinemic effect of orlistat in Gunn rats is partially due to increased metabolism of UCB to derivatives (17). Others have also shown the importance of the intestinal microflora for UCB metabolism (26).…”
Section: Discussionsupporting
confidence: 55%
“…Phototherapy, the routine treatment for neonatal jaundice, has been shown to exert its hypobilirubinemic effect by conversion of UCB into photoisomers (26). Experimental oral treatments, such as orlistat, UDCA, or CaP, are thought to bind UCB within the gut lumen, thereby preventing its reabsorption and interrupting its enterohepatic circulation (13,27,34). Interestingly, both phototherapy and oral treatments have also been suggested to accelerate the gastrointestinal transit.…”
Section: Discussionmentioning
confidence: 99%
“…Bilirubin, Ur, Creat, AST, and ALT were determined by routine spectrophotometry on a P800 unit of a modular analytics serum work area from Roche Diagnostics Ltd. (Basel, Switzerland). We previously found that the total bilirubin concentration in Gunn rat plasma, measured by spectrophotometry, equaled the total UCB concentration, measured by high-liquid performance chromatography after chloroform extraction (17,27).…”
Section: Animalsmentioning
confidence: 92%
See 2 more Smart Citations